La estructura de propiedad de las compañias aéreas y su efecto sobre la prestación de servicios - Bonilla, Jesús Manuel López (2009)
Liberalisation of the economic regulatory regime is the first major challenge of the airline industry.This paper investigated the relationship between ownership structure of airlines and levels of service. It was studied whether public owned airlines will exhibit lower service levels than privately owned airlines. A sample of medium to large international scheduled passenger airlines was used. This work focuses on the passenger satisfaction. Several attributes of service such as check in, information service, courtesy, seat space, comfort, food service, in-flight entertainment services, delays, overbooking, positive word-of-mouth communication, and overall satisfaction were examined. The empirical results of this research showed that public airlines offer less satisfaction levels than private airlines and mixed airlines. However, there were not significant differences between mixed airlines and private airlines when both the types were compared.